Seafarers' mental health status and life satisfaction: Structural equation model - Baygi, Fereshteh; Smith, Andrew; Mohammadian Khonsari, Nami; Mohammadi-Nasrabadi, Fatemeh; Mahmoodi, Zohreh; Mahdavi-Gorabi, Armita; Qorbani, Mostafa (Frontiers in Public Health, 2022)
Background: A variety of factors influence seafarers' health. Such factors might affect their satisfaction with life. Aims: To examine the relationships between seafarers’ mental health status and satisfaction with life by using a structural equation method. Methods: In this survey, 470 seafarers were selected via convenience sampling method from two shipping companies. Validated questionnaires including Satisfaction with Life Scale (SWLS), generalized anxiety disorder-7 (GAD-7), Posttraumatic Stress Disorder-8 (PTSD-8), Patient Health Questionnaire-9 (PHQ-9), General Health Questionnaire-12 (GHQ-12), Perceived Health status and Depression-Anxiety-Stress scale-21 (DASS-21) were used to assess different aspects of well-being and life satisfaction. The stratified path analysis method was applied to analyze the data. Results: 439 seafarers (200 officers and 237 non-officers) with a mean age of 34.5 (SD: 8.05) participated in the current study. The GHQ score directly affected satisfaction with life in both officers (β= 0.35) and non-officers (β= 0.40). Also, perceived health status directly and indirectly affected satisfaction with life among officers (β= 0.19) and non-officers (β= 0.06). While officers working days per month indirectly impacted satisfaction with life through the general anxiety disorder, perceived health status, depression, anxiety, stress and current mental health. In non-officers, generalized anxiety disorder had the most potent indirect effects on satisfaction with life through perceived health status and current mental health. Conclusion: Perceived health status, directly and indirectly, affected seafarers’ satisfaction with life. Measures should be taken in order to improve seafarers’ perceived health status and its effects on satisfaction with life.